Poster: The role of mathematical disciplines in engineering practice - Rozhkova, Svetlana V. (Mobility for smart cities and regional development - challenges for higher education : proceedings of the 24th International conference on interactive collaborative learning (ICL2021))
The article describes mathematical education as an essential part of modern engineers' fundamental training system. The research determines the role of mathematics for engineering practice by analyzing responds of survey experts: engineers with PhD and doctoral degrees in the fields of natural sciences and technology and representatives of acting industrial enterprises of Russia. The purpose of this study is to analyze the role of mathematics in engineering practice. Additionally, the task of the paper is to analyze the relationship between students 'experience with school mathematics and their choice of an engineering career. The research uses the Likert scale as the ground basis. As a result of the study, a link was established between the level of proficiency in mathematics at school and the subsequent choice of an engineering specialty by respondents. Over 80% of responding engineers were successful in mathematics at school. High school students, who are successful in mathematics, continue their success as university students. The quality of mathematical education both in high school and at university has a great influence on future engineers. The study showed that professional engineers constantly use mathematical knowledge in their work.